Espacios de riesgos causados por los cambios en los usos y coberturas del suelo en la parroquia Tixán, cantón Alausí, provincia de Chimborazo - Flores Torres, Steeven David (2022)
The present study analyzed the change of land use and cover of the Tixán parish of the Alausí cantón, province of Chimborazo, in three periods: 1990-2000; 2008-2014; and 2016- 2018; to establish the risk spaces of the parish. Free access information from the "Interactive Environmental Map" technological system of the Ministry of the Environment of Ecuador was used; ArcGIS 10.5 software and an Excel spreadsheet. The methodology was structured in four integral parts: delimitation of the land use and cover maps for the different years; overlay of maps with a scale of 1:125,000 and determination of the changes during the analysis period through a cross-tabulation; analysis of causes and effects, description of risk areas; and, the characterization of risk spaces. The results indicated that the main changes made in the three periods of Tixán are due to production systems, such as the change from agricultural mosaic to forest plantation, logging activity; from Pastureland to Agricultural Mosaic and Pastureland, due to the need to plant in fertile soils for the production of food for livestock, causing the extension of the agricultural frontier; the disappearance of the body of natural water existing in the parish until 2014, due to the uncontrolled use of land for crops and pastures; among other changes that have serious repercussions on the ecosystem services provided by the soil itself, the Pastureland, and native forests, spaces characterized as at risk. Keywords: Land use change, Geographic Information Systems, cartography, spatial analysis, cross-tabulation, map overlay.